Study Literatur: Business Communication Skills - Kayla Naveeza Putri; Zalfaa Aadilah; Mitrayani Timoty; Mada Aditia Wardhana (Shofanah Media Berkah, 2026)
Effective business communication skills constitute critical capital for the success of organizations and individuals in the global marketplace. This article review aims to analyze the effectiveness of pedagogical approaches and psychological factors in developing such competencies. Specifically, the study addresses two research questions: (1) the effectiveness of integrating active learning strategies (Problem-Based Learning and Experiential Learning) and multimedia technology in enhancing students’ business communication competence, and (2) the role of communicative self-efficacy and knowledge transfer capability in supporting successful negotiation and the development of professional relationships. Using a systematic review method that includes identification, selection, extraction, thematic analysis, and synthesis of selected articles, this review concludes that technology-based active learning approaches significantly bridge the theory–practice gap by facilitating the creation of contextual knowledge (Mode 2). Furthermore, the synergy between high self-efficacy and boundary-spanning capacity in knowledge transfer is shown to be a key determinant of communication effectiveness in complex negotiations and workplace relationships. The implications suggest that the holistic development of business communication competence requires the integration of technology-enhanced pedagogical innovation and the strengthening of individual psychological factors.